2011
DOI: 10.2527/jas.2010-3269
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ractopamine hydrochloride on gene expression in adipose tissues of finishing pigs1

Abstract: The long-term effect of feeding the catecholamine analog ractopamine (RAC; ractopamine hydrochloride, Elanco Animal Health, Indianapolis, IN) on the expression of genes involved in energy and lipid metabolism in subcutaneous adipose tissue was studied. Large White pigs (84 kg) were fed corn- and soybean meal-based diets supplemented with 0, 20, or 60 mg/kg of RAC for 14, 28, or 42 d. Expression (mRNA abundance) in adipose tissue of sterol regulatory binding protein-1 (SREBP-1), PPARα, PPARγ2, fatty acid syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
0
20
1
1
Order By: Relevance
“…Other studies have shown that BAA use could reduce adipose tissue and increase fat cell apoptosis (Eadara et al 1989). Further, in pigs, RAC effects were observed in the AMPc pathway genes, such as reduction of FAS and GLUT-4 in adipose tissue (Halsey et al 2011). However, in this study, probably due to the stress, an opposite effect was observed related to that expected from the RAC, suggesting increased lipogenesis.…”
Section: Discussioncontrasting
confidence: 55%
“…Other studies have shown that BAA use could reduce adipose tissue and increase fat cell apoptosis (Eadara et al 1989). Further, in pigs, RAC effects were observed in the AMPc pathway genes, such as reduction of FAS and GLUT-4 in adipose tissue (Halsey et al 2011). However, in this study, probably due to the stress, an opposite effect was observed related to that expected from the RAC, suggesting increased lipogenesis.…”
Section: Discussioncontrasting
confidence: 55%
“…Before slaughter in this experiment, the animals were fasted for 12 h. Thus, SAT, RPAT, and MT were obtained after slaughter and may not reflect the actual scenario of the amount of active enzymes in the adipose tissue of living animals. In the works of Halsey et al (4) and Reiter et al (3), pigs were slaughtered without any period of food deprivation, which may be reflected in the results obtained by these authors. Liu et al (25), however, did not explain whether the animals in their experiment were fasted or not, but their results showed that RAC did not affect the amount of GLUT4 mRNA present in the adipose tissue of the animals.…”
Section: Discussionmentioning
confidence: 83%
“…However, in contrast to the results of Halsey et al (4) and Reiter et al (3), this result was obtained only with the amount of GLUT4 present in the skeletal muscle tissue of animals ( Figure 4). Halsey et al (4) found that 28 days of supplementation with RAC was able to decrease the amount of GLUT4 mRNA present in the adipose tissue of the animals. Reiter et al (3), while increasing the time of exposure to the agonist (52 days), were able to obtain similar results for GLUT4 mRNA present in the adipose tissue and further proved that the same effect (decrease) was also found in skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pigs, another action of ractopamine on fat metabolism is the promotion of lower fat accretion by reducing lipogenesis (Bergen, 2001), which could be explained by the reduction of the sensitivity on adipose tissue to insulin, as it happens in pigs under βAA stimulation, and an evidence of lipogenesis inhibition (Mills et al, 2002). Furthermore, according to recent works focusing on lipogenic gene expression in the adipose tissue of finishing pigs, ractopamine can reduce the RNA transcription of genes related to lipid synthesis, such as sterol regulatory binding protein-1 (SREBP-1), which is a transcriptional factor that drive genes involved in the synthesis of fatty acids (Horton et al, 2003) and fatty acid synthase (Reiter et al, 2007;Halsey et al, 2011), a key enzyme involved in the synthesis of fatty acids (Ferreira et al, 2013). Although no difference was found in the weight gain between control and treatment groups during the experimental period (average of 170 g) ( Table 3), considering that ractopamine may have more efficacy on blocking lipogenesis instead of stimulating lipolysis (Mills et al, 2003), the animals that received ractopamine may have had a decrease of lipogenesis rate, especially at 8 mg kg −1 of ractopamine.…”
Section: Discussionmentioning
confidence: 99%